Management of personal data by students of the Faculty of Mathematics, Physics, and Computer Science in social networks - Rivero, Manuel Osvaldo Machado; Bravo, Leyany María Álvarez (Advanced Notes in Information Science, 2024)
This study described the behavior of students of the Faculty of Mathematics, Physics, and Computer Science (FMFC) regarding the management of personal data (PD) in social networks (SNs). It was a non-experimental, descriptive, and cross-sectional study. A questionnaire was applied to a probabilistic purposive sample of 159 students of the FMFC, where subjects were chosen from all years and careers in an approximate number and not less than 40% of the total enrollment of each year. The SNs most used by the respondents were WhatsApp and Facebook. First and last names, voice messages, age, and photos were the PD most shared on the networks; this occurred mainly with family and friends. To protect the data, students prefer to change the password from time to time since their main concern is to publish in SNs using their name; therefore, they attached greater importance to cancel their PD in case of being used inappropriately. Personal data breaches were only reported on the SN Facebook. Social networks are platforms for interaction and flow of an increasing volume of personal and general data, and there is a high risk that they may be violated due to the lack of knowledge of the users themselves.